Contemporary avenues in catalytic P-H bond addition reaction: a case study of hydrophosphination - Koshti, Vijay; Gaikwad, Shahaji R.; Chikkali, Samir H. (Coordination Chemistry Reviews, 2014)
Remarkable advances and current state-of-the-art developments in catalytic hydrophosphination of alkenes and alkynes are reviewed. The challenges in constructing a C P bond with a special emphasis on metal catalysed (asymmetric) hydrophosphination are highlighted. Only those systems that unambiguously proceed via P H bond addition across a C-C/X (X = O, N, S) multiple bond have been covered in this overview. Reviewed examples support the assumption that either strongly chelating ligands or reaction products that act as ligands, enhance the rate of hydrophosphination. The asymmetric variant of this transformation allows installation of p-chiral [enantiomeric excess (ee) up to 82%] as well as C-chiral (ee up to 99%) centres. The limited spectroscopic, mechanistic data and OFT calculations point at two distinctly different mechanisms. In case of hydrophosphination, the metal undergoes oxidative addition and reductive elimination steps (in general), thus changing the oxidation state from M(0) to M(II) and back to M(0). Whereas in asymmetric hydrophosphination it is proposed that the oxidation state of the metal remains unaltered throughout the catalytic cycle. The examples described in this overview showcase the real power of catalytic hydrophosphination in constructing various phosphorus compounds, which may initiate a new era in organo-phosphorus chemistry. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Alkynes; Asymmetric hydrophosphination; Hydrophosphination; Metal catalyzed hydrophosphination; Olefins; P-H bond addition

Cross-metathesis of biorenewable dioxalates and diols to film-forming degradable polyoxalates - Rajput, Bhausaheb S.; Ram, Farsa; Menon, Shamal K.; Shanmuganathan, Kadhiravan; Chikkali, Samir H. (Journal of Polymer Science Part A-Polymer Chemistry, 2018)
Starting from commonly available sugar derivatives, a single step protocol to access a small family of isohexide-dioxalates (2a-c) has been established. The synthetic competence of 2a-c has been demonstrated by subjecting them to condensation polymerization. Quite surprisingly, the proton NMR of poly(isomannide-co-hexane)oxalate revealed a 1:2 ratio between isomannide-dioxalate (2a) and 1,6-hexanediol (3a) in the polymer backbone. This intriguing reactivity was found to be an outcome of a cross metathesis reaction between 2a and 3a. The cross metathesis products 3a[2-(2-methoxyacetoxy)ethyl 2-(2-hydroxyethoxy)-2-(3-oxydanylidene)acetate] and 2a(3R,6R)-6-hydroxyhexahydrofuro[3,2-b]-furan-3-yl methyl oxalate were isolated in a control experiment. Based on direct and indirect evidence, and control experiments, an alternative polymerization mechanism is proposed. Polymerization conditions were optimized to obtain polyoxalates P1(2a-3a)-P9(2c-3c) with molecular weights in the range of 14,000-68,000 g/mol, and narrow polydispersities. The identity of the polyoxalates was unambiguously established using 1-2D NMR spectroscopy, MALDI-ToF-MS, and GPC measurements. The practical implication of these polymers is demonstrated by preparing transparent, mechanically robust films. The environmental footprint of the selected polyoxalates was investigated by subjecting them to solution and solid-state degradation. The polyoxalates were found to be amenable to degradation. (c) 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2018, 56, 1584-1592

C (1)-Symmetric diphosphorus ligands in metal-catalyzed asymmetric hydrogenation to prepare chiral compounds - Sen, Anirban; Chikkali, Samir H. (Organic & Biomolecular Chemistry, 2021)
Asymmetric hydrogenation has remained an important and challenging research area in industry as well as academia due to its high atom economy and ability to induce chirality. Among several types of ligands, chiral bidentate phosphine ligands have played a pivotal role in developing asymmetric hydrogenation. Although C-2-symmetric chiral bidentate phosphine ligands have dominated the field, it has been found that several C-1-symmetric ligands are equally effective and, in many cases, have outperformed their C-2-symmetric counterparts. This review evaluates the possibility of the use of C-1-symmetric diphosphorus ligands in asymmetric hydrogenation to produce chiral compounds. The recent strategies and advances in the application of C-1-symmetric diphosphorus ligands in the metal-catalyzed asymmetric hydrogenation of a variety of C=C bonds have been summarized. The potential of diphosphorus ligands in asymmetric hydrogenation to produce pharmaceutical intermediates, bioactive molecules, drug molecules, agrochemicals, and fragrances is discussed. Although asymmetric hydrogenation appears to be a problem that has been resolved, a deep dive into the recent literature reveals that there are several challenges that are yet to be addressed. The current asymmetric hydrogenation methods mostly employ precious metals, which are depleting at a fast pace. Therefore, scientific interventions to perform asymmetric hydrogenation using base metals or earth-abundant metals that can compete with established precious metals hold significant potential.

Controlled di-lithiation enabled synthesis of phosphine-sulfonamide ligands and implications in ethylene oligomerization - Mote, Nilesh R.; Gaikwad, Shahaji R.; Khopade, V, Kishor; Gonnade, Rajesh G.; Chikkali, Samir H. (Dalton Transactions, 2021)
Catalyst design for ethylene oligomerization has attracted significant interest. Herein, we report the synthesis of phosphine-sulfonamide-derived palladium complexes and examine their performance in ethylene oligomerization. Arresting a dilithiation intermediate of N-(2-bromophenyl)-4-methylbenzenesulfonamide (1) at -84 degrees C selectively produced N-(2-(bis(2-methoxyphenyl)phosphanyl)phenyl)-4-methylbenzenesulfonamide (L1A). However, the same reaction at -41 degrees C delivered a different ligand; 2-(bis(2-methoxyphenyl)phosphanyl)-4-methyl-N-phenylbenzenesulfonamide (L2A). The generality of our strategy has been demonstrated by preparing N-(2-(diphenylphosphanyl)phenyl)-4-methylbenzenesulfonamide (L1B) and 2-(diphenylphosphanyl)-4-methyl-N-phenylbenzenesulfonamide (L2B). Subsequently, L1A and L1B were treated with a palladium precursor to yield 5-membered complexes C1 and C2, respectively. In contrast, L2A upon treatment with palladium produced a 6-membered metal complex C3. Thus, a small library of 7 palladium complexes (C1-C7) were synthesized by varying the donor moiety (pyridine, DMSO, and acetonitrile). The identity of palladium complexes was unambiguously ascertained using a combination of spectroscopic and analytical methods, including single-crystal X-ray diffraction. The performance of the complexes C1-C7 was investigated in ethylene oligomerization and almost all of them were found to be active. The resultant ethylene oligomers were characterized using H-1 and C-13 NMR, MALDI-ToF-MS, and GPC. Detailed screening of reaction parameters revealed 100 degrees C and 40 bars ethylene to be optimal conditions. Complex C5 outperformed other complexes and produced ethylene oligomers with a molecular weight of 1000-1900 g mol(-1).

Computational insights into the iron-catalyze d magnesium-me diate d hydroformylation of alkynes - Sharma, Himanshu; Tewari, Tanuja; Chikkali, Samir H.; Vanka, Kumar (Journal of Organometallic Chemistry, 2023)
Iron is one of the most abundant transition metals in the earth's crust. It has attracted a lot of attention due to its low toxicity, bio-compatibility, and high natural abundance. Iron-catalyzed hydroamination, hydroalkoxylation, hydrocarboxylation, hydrosilylation, hydroboration, hydrophosphination, hydromagnesiation, and carbonylation reactions have therefore been developed over the past decades. However, despite many experimental and theoretical studies, a complete mechanistic understanding of iron-catalyzed hydrofunctionalisation at the molecular level has not yet been achieved. In this work, through density functional theory (DFT) calculations, we have shown the most feasible path for the hydroformylation of alkynes for an experimentally studied system. We have looked at the iron salt as a precatalyst without any external donor ligand, and the calculations revealed that hydrometalation followed by beta-hydride elimination was favorable over the direct migration of the beta-hydrogen to carbon. Furthermore, our calculations show that the solvent plays an important role in the hydromagnesiation reaction. Furthermore, we have employed an explicit solvent model, where the attachment of one molecule of solvent to the iron center was seen to stabilize the transition states significantly.(c) 2023 Elsevier B.V. All rights reserved.
Keywords: Computational study; Ethylene Assisted Catalysis; EtMgBr Assistance; Explicit Role of Solvent; Hydroformylation; Iron Catalyst